Ellen Redling, and Peter Paul Schnierer, eds. Non-Standard Forms of Contemporary Drama and Theatre. Trier: Wissenschaftlicher, 2008. 257 pp. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The present book is volume fifteen appearing in the series “Contemporary Drama in English” (general editor: Martin Middeke), for which papers from the sixteenth annual conference of the German Society for Contemporary Theatre and Drama in English have been selected. It is a society during the history of which volunteering members have organized well-attended and professionally memorable conferences at respective universities across the German-speaking countries every year. Appropriately, according to the established practice of the society these meetings always host experts of drama and theatre from Britain and/or Ireland whose discussions of aspects of the field provide the program with the insiders’ points of view. Beside the works of some English scholars the present volume naturally includes contributions from Germany, from one or two other European countries and from the United States, offering an attractive range of approaches and opinions.